The Concept of Profit Sharing in The Industrial Field in Islamic Economic - Mujahidin Mujahidin (Al-Kharaj: Journal of Islamic Economic and Business, 2021)
Profit sharing schemes are very limited compared to fixed income schemes, murabaha and ijarah  contracts are far more widely used by Islamic financial institutions than profit sharing schemes. the purpose of this research is to know the concept of profit sharing in the industrial field in islamic economy. This research method uses systematic literature review Literature review aims to make an analysis and synthesis of existing knowledge related to the topic to be researched to find empty space for research to be carried out. The results of this study found that Sharia Banking stipulates that mudharabah  is what is meant by "Akad mudharabah " in Financing is a joint venture agreement between the first party (malik, shahibul mal, or Sharia Bank) which provides all the capital and the second party („factor, mudharib, or the Customer) who acts as fund manager by sharing business profits in accordance with the agreement set forth in the Akad, while the loss is fully borne by the Islamic Bank unless the second party makes a deliberate mistake, is negligent or violates the agreement. based on careful calculations between the three schemes, viz revenue sharing, gross profit sharing and net Profit sharing, hence the schematic profit sharing is the most profitable for tile entrepreneurs in developing their production business.